1991
DOI: 10.1530/acta.0.1240516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytidine 5'-diphosphocholine administration on basal and growth hormone-releasing hormone-induced growth hormone secretion in elderly subjects

Abstract: The basal and GH-releasing hormone-stimulated secretion of GH declines in the elderly. We tested the ability of cytidine 5'-diphosphocholine, a drug used in the treatment of stroke and Parkinson's disease, to alter GH secretion in 11 healthy elderly volunteers, aged 69\ x=r eq-\ 84. Each subject received an iv infusion of 2 g of cytidine 5'-diphosphocholine or normal saline. GHRH and TRH were also administered during cytidine 5'diphosphocholine infusions. The infusion of cytidine 5'-diphosphocholine induced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Since brain acetylcholine (Ach) synthesis declines with aging (Gibson, Peterson and Jenden 1981), it may be possible to restore normal GH secretion by enhancing cholinergic tone. We have recently shown that the putative Ach precursor CDP-choline is able to increase both basal and GHRH induced GH secretion in elderly human subjects (Ceda, Ceresini, Denti, Magnani, Marchini, Valenti and Hoffman 1991), lending support to the hypothesis of an increased somatostatin tone during aging.…”
Section: Introductionmentioning
confidence: 57%
“…Since brain acetylcholine (Ach) synthesis declines with aging (Gibson, Peterson and Jenden 1981), it may be possible to restore normal GH secretion by enhancing cholinergic tone. We have recently shown that the putative Ach precursor CDP-choline is able to increase both basal and GHRH induced GH secretion in elderly human subjects (Ceda, Ceresini, Denti, Magnani, Marchini, Valenti and Hoffman 1991), lending support to the hypothesis of an increased somatostatin tone during aging.…”
Section: Introductionmentioning
confidence: 57%
“…GHRH is the hypothalamic hormone that triggers secretion of GH from the pituitary. The observation that both CDP-choline [49] and choline alphoscerate [50] improve the age-related decline in GH responsiveness to GHRH, further strengths the cholinergic activity of the compounds. The interference with mechanisms of GH release suggests that the two compounds may be also considered for other indications besides the most documented in cognitive domains.…”
Section: Discussionmentioning
confidence: 85%
“…In clinical pharmacology settings they counter the amnesia induced by the cholinergic muscarinic receptor antagonist scopolamine [47,48]. Moreover, CDPcholine and choline alphoscerate counter the age-related decline of both growth hormone (GH) synthesis and release [49,50]. GH decline is associated with cognitive impairment occurring in the elderly [51] and cholinergic system is an important part of mechanisms regulating GH release stimulated by growth hormone-releasing hormone (GHRH) [52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the effects of citicoline on the cholinergic system, together with the other actions on other neurotransmitters and its neuroprotective/neurorestorative properties, could explain the The use of citicoline in healthy adult individuals induces an increase of growth hormone secretion and a decrease on prolactin secretion [241,242].…”
Section: Experimental Datamentioning
confidence: 99%